The Intergenerational Welfare State and the Rise and Fall of Pay‐as‐you‐go Pensions. (26th August 2016) - Andersen, Torben M.; Bhattacharya, Joydeep
Abstract : This article develops a theory of the two‐armed intergenerational welfare state, consistent with key features of modern welfare arrangements, and uses it to rationalise the rise and fall in generosity of Pay‐as‐you‐go Pensions solely on efficiency grounds. By using the education arm, a dynamically‐efficient welfare state is shown to improve upon long‐run laissez faire even when market failures are absent. To release these downstream welfare gains without hurting any transitional generation, help from the pension arm is needed. In the presence of an intergenerational education externality, pensions initially rise in generosity but can be replaced by fully funded pensions eventually.